KAJIAN SOSIOLOGI SASTRA TERHADAP NILAI DAN NORMA SOSIAL DALAM DRAMA “BLONG” KARYA MIJIL PAWESTRI - Mita Marisa Nirditaranti; Firnanda Putria Ananta; Tisya Rexa Oktavia; Akhmad Fatoni (Jurnal Padamu Negeri, 2026)
This study aims to describe the social values ​​and norms contained in Mijil Pawestri's drama "BLONG." This drama depicts domestic life, addressing various social issues, particularly those concerning loyalty, responsibility, and shifting values ​​in modern society. The research method used is a qualitative descriptive approach with a sociology of literature approach according to Wellek and Warren, which emphasizes the reciprocal relationship between the literary work, the author, and society. The data source for this study is the text of Mijil Pawestri's drama "BLONG," while supporting data were obtained through literature review relevant to the theory and social context of the work. Data collection was conducted using reading and note-taking, then analyzed by identifying intrinsic elements and relating them to the social realities depicted in the text. The results show that the drama "BLONG" reflects several social values, such as loyalty, hard work, and responsibility, and incorporates social norms such as family norms, economic norms, and moral norms. This drama also provides a glimpse into changes in societal behavior and attitudes toward modernity and materialism. Thus, this work serves not only as entertainment but also as a social mirror reflecting the dynamics of contemporary society.